Molecular Mechanism of Curcumin and Its Analogs as Multifunctional Compounds against Pancreatic Cancer. (13th August 2022) - Huang, Qun; Zhang, Ya; Zheng, Yanlin; Yang, Hongjing; Yang, Yang; Mo, Ya; Li, Liuying; Zhang, Hong
Abstract: Pancreatic cancer (PC) is one of the most common malignant tumors with a poor prognosis and high mortality. Surgical resection is the most effective treatment for PC; however, only a minority of patients have resectable tumors. Chemotherapy is the primary treatment for PC. Curcumin is a natural chemical substance obtained from plants with a wide range of pharmacological activities. Research evidence suggests that curcumin can influence PC development through multiple molecular mechanisms. The synthesis of novel curcumin analogs and preparation of curcumin nano-formulations are effective strategies to overcome the low bioavailability of curcumin in the treatment of PC. This review aims to summarize the mechanisms of action of curcumin in preclinical and clinical studies on PC and research progress in enhancing its bioavailability.